Analisis Penerapan Akuntansi Murabahah Dalam Pembiayaan KPR Pada Bank Syariah Indonesia (BSI) Cabang Karawang - Syifa Ardiyani; Nana Diana (Peneliti.net, 2023)
This study aims to analyze the application of murabahah contracts in sharia mortgage and its adjust to Pernyataan Standar Akuntansi Keuangan (PSAK) 102 regarding murabahah accounting at Bank Syariah Indonesia Karawang Branch. This study used a descriptive qualitative method and data collection technique in the form of interviews and some secondary data from report documents. Based on the research results, it can be known that the application of the murabahah accounting at Bank Syariah Indonesia Karawang Branch refers to PSAK 102 and basically complies with the applicable regulations.